The Institutionalization of Islamic Education through Tradition, Habituation, and Adaptation: Lessons from Islamic Boarding School on Sumbawa Island - Halimah Halimah; Khozin Khozin (Lembaga Bale Literasi, 2026)
This study aims to analyze strategies for strengthening Islamic educational institutions within islamic boarding school (Islamic boarding schools) and to formulate a strengthening model based on tradition, habituation, and adaptation. A qualitative approach with a case study design was employed, focusing on a specific islamic boarding school in Indonesia. Data were collected through semi-structured interviews, observations, and document analysis, involving 14 informants comprising islamic boarding school leadership, administrators, teachers (ustadz), and students (santri). The data were analyzed using thematic analysis, involving repeated reading, coding, categorization, and the formulation of key themes. The results indicate that the institutional strengthening of Islamic education does not occur in a piecemeal fashion but rather through eight interconnected strategies: consolidating institutional values; integrating Islamic education curricula and programs; strengthening the roles of islamic boarding school actors; revitalizing Islamic scholarly traditions; fostering character through habituation and discipline; developing educator resources; establishing institutional partnerships; and adapting to technology and social change. These findings underscore that Islamic education in islamic boarding school functions not merely as formal instruction but as a living value system embedded in the institution's structure, culture, social relations, and the students' daily practices. The study's primary contribution is the formulation of an institutional strengthening model for Islamic education conceptualized as an